Ḥikmah (wisdom) pedagogy and students’ thinking and reasoning abilities - Hashim, Rosnani; Hussien, Suhailah; Imran, Adesile (IIUM Press, 2014)
This research drew on the authors’ long experience in the implementation of the “Hikmah Pedagogy” which is based on the Philosophy for Children’s teaching method. Specifically, the study examined the influence of the pedagogy on the participants’ perceptions of and feelings about their thinking and reasoning skills. The sample comprised 188 Malaysian and international students from an international secondary school in Malaysia. This consisted of students in four Grade levels, ranging from Grades 7 to 10. An instrument named “Hikmah Feedback Survey - HFS” was employed for data collection. The findings were supportive of the positive influence of the pedagogy on students’ abilities to think and reason better after experiencing the programme. Furthermore, the participants demonstrated a considerable improvement in their cognitive and social-communicative skills, as evidenced in the scores obtained for the post-programme’s test. This affirms the fact that the ḥikmah pedagogy is highly recommended in Malaysia’s march towards its Vision 2020 developmental goals. Implications of the study were discussed and suggestions were proposed to educators and stakeholders in secondary school education.